TH1 and TH17 cells promote crescent formation in experimental autoimmune glomerulonephritis. Issue 1 (11th June 2015) - Hünemörder, Stefanie; Treder, Julia; Ahrens, Stefanie; Schumacher, Valéa; Paust, Hans‐Joachim; Menter, Thomas; Matthys, Patrick; Kamradt, Thomas; Meyer‐Schwesinger, Catherine; Panzer, Ulf; Hopfer, Helmut; Mittrücker, Hans‐Willi
Abstract Autoimmunity against the Goodpasture antigen α3IV‐NC1 results in crescentic glomerulonephritis (GN). Both antibodies and T cells directed against α3IV‐NC1 have been implicated in disease development and progression. Using the model of experimental autoimmune glomerulonephritis (EAG) in DBA/1 mice, we aimed to characterize the frequency and function of α3IV‐NC1‐specific CD4+ T cells in the kidneys. DBA/1 mice repeatedly immunized with human α3IV‐NC1 developed necrotizing/crescentic GN. Kidneys with crescentic GN contained CD4+ cells responding to α3IV‐NC1 with the production of IFN‐γ or IL‐17A, demonstrating the accumulation of both α3IV‐NC1‐specific TH1 and TH17 cells. To test the functional relevance of TH1 and TH17 cells, EAG was induced in DBA/1 mice deficient in IFN‐γR, IL‐17A or IL‐23p19. Mice of all knockout groups mounted α3IV‐NC1 IgG, developed nephrotic range proteinuria, and IgG deposition to the glomerular basement membranes at levels similar to immunized wild‐type mice. However, all knockout groups showed significantly fewer glomerular crescents and attenuated tubulointerstitial damage. Our results suggest that both α3IV‐NC1‐specific TH1 and TH17 cells accumulate in the kidneys and are crucial for the development of necrotizing/crescentic GN. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.